La Soufrière - Herzog, Werner; Lachman, Ed; Schmidt-Reitwein, Jörg (Filmedition Werner Herzog, 2010)
"La Soufrière" is, as Herzog explains, a documentary of an unavoidable catastrophe that didn’t happen. When Herzog learned in 1977 that the volcano, La Soufrière, on the small Caribbean island of Guadaloupe was about to explode and that one man had decided to stay behind, he assembled a small and daring crew and went to interview the man ... What makes "La Soufrière" a particularly beguiling film is Herzog’s banal tone. As is clear, almost from the outset, the volcano didn’t erupt. Yet Herzog insists that during his entire time of the island, the ground shook and the volcano may have been minutes from exploding. In hindsight, he realizes the idiocy of his traveling there and attempting to capture the explosion, the idiocy of sacrificing himself and his crew for apocalyptic footage and some insight into the meaning of life and death. What he comes away with is a striking rumination on absurdity. [www.filmcritic.com]